Mild Intrauterine Hypoperfusion Leads to Lumbar and Cortical Hyperexcitability, Spasticity, and Muscle Dysfunctions in Rats: Implications for Prematurity - Coq, Jacques-Olivier; Delcour, Maxime; Ogawa, Yuko; Peyronnet, Julie; Castets, Francis; Turle-Lorenzo, Nathalie; Montel, Valérie; Bodineau, Laurence; Cardot, Phillipe; Brocard, Cécile; Liabeuf, Sylvie; Bastide, Bruno; et al. (Frontiers in Neurology, 2018)
Intrauterine ischemia-hypoxia is detrimental to the developing brain and leads to white matter injury (WMI), encephalopathy of prematurity (EP), and often to cerebral palsy (CP), but the related pathophysiological mechanisms remain unclear. In prior studies, we used mild intrauterine hypoperfusion (MIUH) in rats to successfully reproduce the diversity of clinical signs of EP, and some CP symptoms. Briefly, MIUH led to inflammatory processes, diffuse grey and WMI, minor locomotor deficits, musculoskeletal pathologies, neuroanatomical and functional disorganization of the primary somatosensory and motor cortices, delayed sensorimotor reflexes, spontaneous hyperactivity, deficits in sensory information processing, memory and learning impairments. In the present study, we investigated the early and long-lasting mechanisms of pathophysiology that may be responsible for the various symptoms induced by MIUH. We found early hyperreflexia, spasticity and reduced expression of KCC2 (a chloride cotransporter that regulates chloride homeostasis and cell excitability). Adult MIUH rats exhibited changes in muscle contractile properties and phenotype, enduring hyperreflexia and spasticity, as well as hyperexcitability in the sensorimotor cortex. Taken together, these results show that reduced expression of KCC2, lumbar hyperreflexia, spasticity, altered properties of the soleus muscle, as well as cortical hyperexcitability may likely interplay into a self-perpetuating cycle, leading to the emergence and persistence of neurodevelopmental disorders in EP and CP, such as sensorimotor impairments, and probably hyperactivity, attention and learning disorders.